2015
DOI: 10.3311/ppch.7839
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Toxicity Assessment of the Spilled Ajka Red Mud in Soil Microcosms for Its Potential Utilisation as Soil Ameliorant

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 37 publications
5
35
0
Order By: Relevance
“…However, the elevated CFU was preserved only at 5% RM dose until the 8 th month. Based on chemical, biological and ecotoxicological results Ujaczki et al, 2015 concluded that RM could be mixed at up to 5% into the soil without any mid-term adverse effect on the Ajka soil as natural habitat. This finding substantiated the recommended remediation option in the area: excavation of the RM flooded soil together with the overlain RM layer and storing of the excavated red mud and soil mixture (RMSM) in Ajka behind the red mud storage area.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the elevated CFU was preserved only at 5% RM dose until the 8 th month. Based on chemical, biological and ecotoxicological results Ujaczki et al, 2015 concluded that RM could be mixed at up to 5% into the soil without any mid-term adverse effect on the Ajka soil as natural habitat. This finding substantiated the recommended remediation option in the area: excavation of the RM flooded soil together with the overlain RM layer and storing of the excavated red mud and soil mixture (RMSM) in Ajka behind the red mud storage area.…”
Section: Discussionmentioning
confidence: 99%
“…Modeling the effects of the RM spill in Ajka Ujaczki et al, 2015 found that the aerobic heterotrophic cell counts (CFU) increased upon max. 40% RM dose into the Ajka soil 2 months after addition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The luminescence intensity was measured with Fluostar Optima microplate reader after 30, 60 and 120 min of contact time. The evaluations of the results were carried out as described by Ujaczki et al [43]. Copper sulphate was used as standard toxicant in all experiments, to check the sensitivity of the Aliivibrio fischeri culture.…”
Section: Test Methods and Evaluation 231 Aliivibrio Fischeri Biolummentioning
confidence: 99%